2012
DOI: 10.1002/14651858.cd000352.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Planned hospital birth versus planned home birth

Abstract: Background Observational studies of increasingly better quality and in different settings suggest that planned home birth in many places can be as safe as planned hospital birth and with less intervention and fewer complications. This is an update of a Cochrane review first published in 1998. Objectives To assess the effects of planned hospital birth compared with planned home birth in selected low-risk women, assisted by an experienced midwife with collaborative medical back up in case transfer should be ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 80 publications
2
99
0
2
Order By: Relevance
“…Among these, one stands out -a systematic review from the Cochrane Library. 1 Practically all confirm that there is a lower rate of obstetric interventions in home births.…”
Section: Introductionmentioning
confidence: 96%
“…Among these, one stands out -a systematic review from the Cochrane Library. 1 Practically all confirm that there is a lower rate of obstetric interventions in home births.…”
Section: Introductionmentioning
confidence: 96%
“…The existing evidence that many medical interventions are overused, while structural and social interventions are often underused, has had limited impact on practice. 9 …”
Section: Introductionmentioning
confidence: 99%
“…3 Recently, however, the value of hospital birth for all women with low-risk pregnancies has come into question; it has been suggested that in the absence of benefit, a planned hospital birth for this population may increase the use of intrapartum interventions, including cesarean delivery. [4][5][6][7] Even though recent studies comparing planned home and hospital births have had moderate sample sizes, they are individually limited in their ability to report definitively on rare outcomes such as death.…”
mentioning
confidence: 99%
“…Owing to a lack of evidence from randomized controlled trials (RCTs) to show that restricting a woman's freedom to choose a place of birth prevents harm, the authors of a 2012 Cochrane review of planned hospital versus planned home births concluded that home birth services with collaborative medical backup should be established and offered to women with low-risk pregnancies in all jurisdictions. 8 This conclusion, along with findings from the large English Birthplace Cohort Study, 4 may be what prompted the National Institute for Health and Care Excellence (NICE) in England to update its intrapartum care guidelines to recommend that, for women at low risk of birth-associated complications, home birth should be considered a generally safe option. 9 With the paucity of information derived from RCTs, 8 observational studies are essential to continue to inform and monitor maternal and infant outcomes for women at low obstetrical risk who plan home or hospital birth, and to continue to provide pregnant women with quality information about choice of birthplace.…”
mentioning
confidence: 99%